Membranous glomerulonephritis and cellular crescents induced by levamisole-adulterated cocaine abuse: a case report - Roca-Argente, Lourdes (Ann Transl Med, 2015)
Levamisole is illicitly employed as a cocaine adulterant. The consumption of levamisole-adulterated cocaine can provoke anti-neutrophil cytoplasmic antibody (ANCA)-associated syndromes. Patients carrying an HLAB27 allele are known to be at higher risk of developing agranulocytosis when treated with levamisole. Likewise, patients with ANCA-associated vasculitis (AAV) and internal organ involvement have typically been exposed to offending agents for prolonged periods of time, often on the order of years. Here, we report an unusual case of a patient in which kidney biopsy showed membranous glomerulonephritis with cellular crescents associated with levamisole-contaminated cocaine use.